The Role of Communication in Developing Remote Learning and Inclusive Education in Lithuania - Leknickienė, Dovilė (Vilnius University Open Series, 2025)
Remote Learning as a Form of Education, characterized by the physical separation of teachers and students and the use of technology, has traditionally targeted non-traditional students, such as working professionals, military personnel, and those living in remote areas. Today, however, remote learning has become particularly relevant for individuals with disabilities, who often demonstrate the highest motivation to pursue skill development and qualification improvement. Environmental changes and technological advancements have spurred a need for a more flexible education system in Lithuania as well. One of the primary goals of remote learning is to develop a socially equitable, accessible education system that enables lifelong learning, helps individuals manage disabilities, and fosters more effective learning. A wide range of experiences highlights the necessity to promote educational flexibility and create opportunities for everyone to learn.This article presents a study conducted to examine the role of communication in developing remote learning and inclusive education in Lithuania. The study employed scientific literature analysis and a qualitative research approach, using semi-structured interviews. The article explores the concept and characteristics of remote learning, identifies the relevance and challenges of remote learning for individuals with disabilities, and examines the functionality of remote learning and the role of communication in these processes.
Keywords: the role of communication; inclusive education; remote learning; adult distance learning